Manufacturing of Aluminum Alloy Parts from Recycled Feedstock by PIG Die-Casting and Hot Stamping - Tatsuhiko Aizawa; Takeshi Kurihara; Hiroki Sakayori (Lubricants, 2022)
PIG (Pin-Injection-Gate) die-casting and hot stamping was developed for fabrication of small-sized and thin-walled aluminum alloy parts from the recycled feedstock. The pure aluminum and aluminum alloy granules were utilized as a feedstock model of recycled materials. The measured mass of granules with the estimated weight from 3D-CAD (Computer Aided Design) of products was poured into the PIG-nozzles before injection. After quickly melting by induction heating inside the PIG-nozzle units, the aluminum melts were injected into a die cavity through the PIG-nozzle. No furnaces and no crucibles were needed to store the melt aluminum stock in different from the conventional die-casting system. No clamping mechanism with huge loading machine was also needed to significantly reduce the energy consumption in casting. Much less wastes were yielded in these processes; the ratio of product to waste, or, the materials efficiency was nearly 100%. Nitrogen supersaturation and TiAlN coating were used to protect the PIG-nozzle and the stamping die surfaces from severe adhesion from aluminum melt. The pure aluminum gears and thin-walled mobile phone case were fabricated by this process. X-ray tomography proved that both products had no cavities, pores and shrinkages in their inside. Using the hot stamping unit, the micro-pillared pure aluminum heatsink was fabricated to investigate the holding temperature effect on the aspect ratio of micro-pillar height to width.